2005
DOI: 10.1016/j.cvsm.2005.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Update on the Etiology of Tooth Resorption in Domestic Cats

Abstract: Feline odontoclastic resorptive lesions (FORL) were first recognized and histologically differentiated from caries in the 1920s [1,2]. Some anecdotal reports describing caries-like lesions at the cervical region of feline teeth followed in the 1950s and 1960s, until two microscopic studies in the 1970s again revealed that FORL were not caries but a type of tooth resorption [3,4]. A recent study showed that cats with FORL have a significantly lower urine specific gravity and significantly higher serum concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
67
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(73 citation statements)
references
References 66 publications
(94 reference statements)
3
67
0
3
Order By: Relevance
“…The etiology of FORL, like that of mICR, remains largely unknown. Suggested etiologic or predisposing factors include furcation anatomy of feline teeth, mechanical stress, diet texture and nutrient content, oral acid levels related to diet or vomitus, irregularities of calcium homeostasis, excess vitamin D, and viral infections (17,18). Some authors also reported a significantly lower occurrence of root replacement resorption by alveolar bone (type II) in cat teeth with resorptive lesions, with the latter presenting roots with a normal radiographic appearance without replacement resorption (type I) (19,20).…”
mentioning
confidence: 99%
“…The etiology of FORL, like that of mICR, remains largely unknown. Suggested etiologic or predisposing factors include furcation anatomy of feline teeth, mechanical stress, diet texture and nutrient content, oral acid levels related to diet or vomitus, irregularities of calcium homeostasis, excess vitamin D, and viral infections (17,18). Some authors also reported a significantly lower occurrence of root replacement resorption by alveolar bone (type II) in cat teeth with resorptive lesions, with the latter presenting roots with a normal radiographic appearance without replacement resorption (type I) (19,20).…”
mentioning
confidence: 99%
“…The condition usually involves multiple permanent teeth and can start anywhere on the tooth's root surface. 99,100 99,100 …”
Section: Tooth Resorptionmentioning
confidence: 99%
“…These findings demonstrate events that occur before obvious tooth resorption and suggest that the very early lesion is probably noninflammatory. 100,101 Several other peculiarities are noted in the permanent teeth of cats that could be associated with tooth resorption, including unusual thickening of alveolar bone (alveolar bone expansion), with or without periodontal pocket formation, and abnormal extrusion of canine teeth (supereruption). 100,101 Resorption of enamel may occur when root resorption has progressed coronally into the crown.…”
Section: Replacement Resorption and Inflammatory Resorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Embora a osteologia mandibular já tenha sido descrita em algumas espécies, a exemplo do homem (Suazo et al, 2007;Kim et al, 2009) e do cão (Villamizar Martinez et al, 2009), a literatura é escassa quanto à osteologia craniana dos felinos, sejam estes domésticos ou provenientes de habitat selvagem (Christiansen, 2008). Sabe-se que várias afecções dentárias dos felinos podem evoluir para uma agressão ou dano ao CM, a exemplo da lesão de reabsorção, necessitando de intervenção cirúrgica (Reiter et al, 2005). Dessa forma, a negligência ou o desconhecimento anatômico dessa região pode repercutir em danos ao organismo animal e, eventualmente, no óbito do paciente (Carvalho, 2004).…”
unclassified